Exposing Althusser’s State Apparatuses through Ishmael Reed’s The Free-Lance Pallbearers - Ali Ahmadi; Azyta Aryan (Critical Literary Studies)
The present research argues that it seems not all writers and their works may fall into an omnipresent ideology trap as Althusser conceives it; or unlike what Althusser holds, not all fictional characters are ‘interpellated”. Therefore, this research gives focal attention to reconsidering Althusser notion of ideology and his Ideological State Apparatus, ISAs, especially the cultural ISA through a descriptive-analytical method. Reed’s novel, The Free-Lance Pallbearers (1967), enjoying circumstantial artistic, religious, ethnic, racial, and literary characters, presents protagonists who not only refute or subvert this domineering ideology but also reshape and redefine it, making it necessary to reconsider Althusserian definition of literature as a cultural ISA. The novel, parodying “the Afro-American tradition of first-person, confessional narratives” is read as a microcosm to repudiate Althusser’s macrocosmic notions of reality. All through, the findings indicate that through the course of the novel, Reed subverts the dominant cultural and ideological discourse of American society through questioning the White standards from language and notions of reality to the ruling system.